Coupling coordination relationship of forestry industry development and ecological environment: evidence from Heilongjiang Province - Zhang, Qi; Kou, Chenhuan; Gao, Wenbo (Frontiers in Environmental Science, 2024)
China's economy has entered a new period of transformation, and the development of various industries will become the backbone of promoting economic sectors. At the same time, it will also become a booster for promoting the transformation and development of various industries. As an essential component of China's economic construction, forestry will also enter a critical period of transformation. However, because the forestry industry mainly relies on forest resources as production factors, there is a certain contradiction between the forestry industry development and the ecological environment. Therefore, taking Heilongjiang Province as an example, this paper applies the PSR model to explain the mechanism of the relationship between forestry industry development and the ecological environment. The PSR model mainly consists of three indicators: Pressure, State, and Response, which analyze the interrelationships between elements within the system. On the other hand, the coupling coordination model is applied to analyze the coupling coordination relationship between the forestry industry development and the ecological environment in Heilongjiang Province from 2011 to 2018. The results show that the development of the forestry industry puts pressure on the ecological environment. At the same time, the environmental climate also imposes restrictions and constraints on the development of the forestry industry. The two promote, influence, and constrain each other. The development of the forestry industry was antagonistic, running in, coupled, and coordinated with the ecological environment in Heilongjiang Province from 2011 to 2018. However, there is still a particular gap in the level of coupling and coordination between the two, and they have yet to reach a state of good coordinated development. Therefore, Heilongjiang Province can promote the coordinated development of its forestry industry and the ecological environment through innovative forestry industry transformation models, policy-oriented rational development and utilization of forest resources, environmentally constrained clean production of the forestry industry, and complementary and shared development of the forestry industry and ecological environment.